Snakes and Ladders Board Game Table Design to Develop Cognitive, Social and Tactual Perception Skills in Blind Children - Anam, Choirul; Priharto, Muria Ilham (International Journal of Recent Technology and Applied Science (IJORTAS), 2021)
This study aims to overcome what is experienced by blind children and to invite blind children to take part in playing and not forgetting to put forward special design aesthetics for blind children. The results found result from primary data collection from observations of the daily activities of the subject and interviews with the subject, teacher, and subject's parents and secondary data got from literacy results from related research sources. The research subjects were taken from students of SDLB-A YPAB SURABAYA. The research method used is design thinking by approaching the subject. In the ultimate result, an innovative traditional snake and ladder game was found which was changed in such a way as to be accessible so that it was more friendly for blind children to use.